The Effect of the Profit Sharing System and Capital Requirements on Financing Decisions for MSMEs in the Culinary Sector in Telanaipura District, Jambi City - Sarmila; Eja Armaz Hardi; Neneng Sudharyati (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the influence of the profit-sharing system and capital requirements on financing decisions of culinary sector MSMEs in Telanaipura District, Jambi City. Culinary sector MSMEs have an important contribution to regional economic growth, but still face capital limitations. The profit-sharing system in Islamic financial institutions is an alternative financing based on partnership and justice, while capital requirements are an internal factor that drives business actors in determining financing decisions. This study uses a quantitative approach with a survey method. Data were obtained by distributing questionnaires to 100 culinary sector MSMEs in Telanaipura District. The data analysis technique used is multiple linear regression with the help of SPSS version 25. The independent variables in this study are the Profit-Sharing System (X₁) and Capital Requirements (X₂), while the dependent variable is the Financing Decision (Y). The results show that the Profit-Sharing System partially has a positive and significant effect on Financing Decisions with a significance value of 0.004 <0.05. Capital Requirements also have a positive and significant effect on Financing Decisions with a significance value of 0.001 <0.05. Simultaneously, both independent variables significantly influence financing decisions, with a significance value of 0.000 < 0.05. This study concludes that the better the perception of MSMEs towards the profit-sharing system and the higher the capital requirement, the stronger the tendency to determine financing decisions.